Meeting Report of the International Conference on the Great Lakes Region’s Regional Training Facility (ICGLR-RTF) and the Population Council - Byamukama, Nathan; Asiimwe, Sharon; Birungi, Harriet (REPRODUCTIVE HEALTH, 2019)
For over a decade, the Population Council and its partners (the Africa Regional SGBV Network) have provided technical assistance and conducted research to strengthen the evidence base of sexual and gender-based violence (SGBV) programming in Africa’s East, Horn, and Great Lakes regions. Under the Africa Regional SGBV Network, the Council and partners developed and tested an intervention including police response to sexual violence survivors, with police provision of emergency contraception (EC) for survivors and referrals to health facilities. This model has been successfully tested in Zambia and Malawi. Studies reveal that EC provision by trained police to sexual violence survivors is both feasible and effective. Results from these studies prompted the Government of Zambia to request Council technical assistance to scale this model nationally, and a meeting was co-convened by the Council and the East African Community Department of Peace and Security in 2014. This meeting report (Sauti/VOICE Program Brief 1) describes meeting objectives and regional recommendations.